2014
DOI: 10.1158/1078-0432.ccr-14-0713
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Activity of the Liposomal Cisplatin Lipoplatin in Ovarian Cancer

Abstract: Purpose: Cisplatin and its platinum derivatives are first-line chemotherapeutic agents in the treatment of ovarian cancer; however, treatment is associated with tumor resistance and significant toxicity. Here we investigated the antitumoral activity of lipoplatin, one of the most promising liposomal platinum drug formulations under clinical investigation.Experimental Design: In vitro effects of lipoplatin were tested on a panel of ovarian cancer cell lines, sensitive and resistant to cisplatin, using both two-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Some second-line chemotherapeutic drugs have been approved for the treatment of ovarian cancer such as paclitaxel, topotecan, etoposide, gemcitabine, and trabectedin [29]. If recurrence occurs within 6 months of the initial treatment, or if it occurs following complete clinical response to chemotherapy including platinum, liposomal paclitaxel can be used alone [30]. However, if recurrence happens after more than 6 months, liposomal paclitaxel Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry may be combined with platinum for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some second-line chemotherapeutic drugs have been approved for the treatment of ovarian cancer such as paclitaxel, topotecan, etoposide, gemcitabine, and trabectedin [29]. If recurrence occurs within 6 months of the initial treatment, or if it occurs following complete clinical response to chemotherapy including platinum, liposomal paclitaxel can be used alone [30]. However, if recurrence happens after more than 6 months, liposomal paclitaxel Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry may be combined with platinum for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LIPO showed anti-tumor effect in CDDP-sensitive-and -resistant ovarian cancer cells since apoptosis was induced by caspases 3, 8, and 9 activation; Bax upregulation; and Bcl-2 downregulation [11] . LIPO caused a synergistic effect combination with doxorubicin and the albumin-bound paclitaxel abraxane.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomal platinum is the most promising drug formulation under clinical conditions [11] . Lipoplatin (LIPO) is a liposomally encapsulated form of CDDP [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies of a liposomal formulation of cisplatin have shown promising effects against ovarian, pancreatic, head and neck cancer, non-small cell lung cancer (NSCLC), and HER-2/neu–negative metastatic breast cancer [53,65,66,67,68]. In ovarian cancer, lipoplatin (liposomal cisplatin) was found to exhibit anti-tumor activity by causing caspase activation and hence apoptosis [65].…”
Section: Alternative Pathways For Accumulation Of Cisplatinmentioning
confidence: 99%